Low Cost Air Pollution Monitoring Machine Using Internet Of Things (Iot) - Aditya Raychowdhury, Abhinav.K, Raushan Kumar, Ritwik Mitra, Dr. A. Mathivanan (International Journal of Modern Agriculture, 2021)
Air pollution monitoring sensor using Internet of Things (IOT) determines the concentration of the various gases released into the atmosphere. The gas sensors in the air pollution monitoring sensor is placed hanging in midair within a PVC pipe and is connected to the (PIC) Programmable interface Microcontroller, (GSM) Global System for Mobile communications using wires, the Inlet fan is fixed on top face of the PVC pipe which sucks air into the PVC pipe for the gas sensors to sense. For operating the system we have to first insert the SIM card into the GSM (Global System for Mobile communications) then we have to login into the Thing speak account in the computer after which we have to connect the battery to circuit and run the circuit and inlet fan after which the LCD (Liquid Crystal Display) will show the concentration of the various gases present in the atmosphere in analog at the same time this reading will be received by the Thing speak account in the computer using IOT and it will plot concentration of gas v/s times graph for various gases present in the atmosphere. This gas sensor can be used to determine the concentration and presence of gases like CO, Methane, Butane, Carbon, Nitrogen dioxide, LPG, CNG, Combustible gases, etc. This system can run in any location for long duration as it is powered using a battery. The conductivity of the gas sensor is directly proportional to the concentration of the harmful gases in the atmospheric air, so the presence of the harmful gases in the air causes a change in the conductivity of the gas sensor which produces a corresponding change in the harmful gas concentration value and hence the concentration of the various harmful gases is determined.